Political justice and religious values - Andrain, Charles F. (Contemporary sociological perspectives series, 2008)
Interpretations of religion and politics -- Political attitudes and religious values -- Political and spiritual justice -- Meaning of justice -- Sources of knowledge about justice -- Application of spiritual principles to public policies -- Religious discourse and political change -- Perspectives on biblical justice -- Interpretations of the Scriptures -- Jesus, justice, and the challenge to elitist rule -- Paul, justice, and citizenship in heaven -- Walter Rauschenbusch : prophet of the social gospel -- Capitalist modernization and the progressive movement -- Theological views about justice -- Public policy preferences for justice -- The social gospel and political action -- Protestant activists -- Jim Wallis -- William Sloane Coffin -- John Shelby Spong -- Dorothy Day : the Catholic worker movement -- Rabbi Michael Lerner : the network of spiritual progressives -- New thought and the power of the individual mind -- The heritage of new thought -- Early Christian gnosticism : the Gospel of Mary -- Transcendentalism : the influence of Ralph Waldo Emerson -- The teacher of new thought : Emma Curtis Hopkins -- The unity school of Christianity -- Religious science -- The policy influence of religious liberalism -- The exercise of political influence -- Religious vision -- Political organization -- Individual support -- Liberal and conservative attitudes toward justice -- The motivational basis of attitudes -- Hypotheses about issue preferences -- National public opinion -- Public opinion among religious groups